Advances In Biosensor Technologies For Breast Cancer Biomolecule Detection: Toward The Development Of Label-Free Biosensing Systems - Manasa, T L; Upadhyay, Dr. Rajesh Kumar; H B, Dr. Divyashree (International Journal of Aquatic Research and Environmental Studies, 2026)
Breast cancer remains one of the leading causes of death among women worldwide and there is a need for rapid and accurate diagnosis to urgently address the issue. The sensitivity, specificity, and monitoring of the detection of breast cancer proteins have significantly improved in recent years due to biosensor technology. This work aimed to systematically review and classify the existing biosensor technologies and to propose an efficient label free biosensing approach for the detection of the breast cancer biomolecules. The methodology involved a detailed literature survey, comparison of electrochemical, optical and piezoelectric biosensors and evaluation of the label free sensing techniques based on nanomaterials. The study of the electrochemical label-free biosensors showed an improvement in their analytical performance with shorter response times and lower detection limits. The research shows that the combining of nanotechnology and unlabelled biosensing devices is a promising, economic and reliable method to early diagnosis of breast cancer and clinical applications.
Keywords: Breast Cancer, Biosensors, Label-Free Biosensing, Nanotechnology, Biomolecule Detection, Electrochemical Biosensors, Cancer Diagnostics.